The role of peptides in regulating dough quality: A comprehensive review - Chaodong Du; Tingting Hong; Guidong Huang; Xianfeng Zhong; Yue Li; Shuhan Zhang; Liwei Fu; Song Zhu (Food Research International, 2026)

Unveiling the pathogenesis and therapeutic strategies of Alzheimer’s disease through cuproptosis - Shuangfeng Xu; Jing Mu; Zhifeng Wang; Jiao Yang; Daman Tian; Ting Shi; Junfeng Lan; Pengfen He; Zhihui Hao; Youchuan Fu; Liwei Xing; Jianzhou Ye; et al. (BioMetals, 2026)

Depositional and Diagenetic Controls on Eyelid–Eyeball Limestones in the Middle Permian Maokou Formation, Sichuan Basin - Zhipeng Chen; Penghui Xie; Lei Chen; Sheng Fu; Gaocheng Wang; Liwei Jiang; Chen Zou (Journal of Marine Science and Engineering, 2026)
The Mao-1 Member of the Middle Permian Maokou Formation in the Yongchuan area contains distinctive eyelid–eyeball limestones developed in an outer-ramp to intraplatform-basin transitional setting. The two components alternate as mud-rich laminae and carbonate-rich nodules or layers. Eyelid limestone contains 10–45% micritic carbonate mud and a mean total-grain content of 69.11%, whereas eyeball limestone contains

A single strain Priestia sp. confers resistance to rice blast through the activation of plant immune responses - Jirong Shi; Mengyao Yan; Jiajie Lou; Qiuyun Liu; Hanrong Qiu; Xinqing Wu; Jiahong Dong; Liwei Sun; Yinhua Ni; Zhengwei Fu; Haifeng Qian; Tao Lu (Physiological and Molecular Plant Pathology, 2026)

Modification of black bean protein isolate-gum Arabic coacervates by Maillard conjugation and tannic acid cross-linking for stable citronella oil microencapsulation - Haifang Mao; Congle Wang; Benu Adhikari; Jie Chen; Liwei Fu; Liqing Qiu (Innovative Food Science & Emerging Technologies, 2026)

Effect of oxidation degree on high-temperature rheological properties and extruded soybean protein - Liwei Fu; Benu Adhikari; Qian Deng; Zhiyong He; Maomao Zeng; Jie Chen; Zhaojun Wang (Food Hydrocolloids, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

Phosphazene derivative synergistically reinforced flexible silicone rubber composites for extreme thermal protection at 2100 °C - Zhao Lu; Yisen Huang; Zhaohui Lu; Xiaochuang Di; Chuxiang Zhou; Hongbin Tian; Bojie Fu; Liwei Yan; Mei Liang; Yang Chen; Huawei Zou (Chemical Engineering Journal, 2026)

Multifunctional trilayer films based on gelatin-dextran incorporated with defatted rice bran-derived carbon dots for scallop preservation - Hongkai Xie; Hailu Liao; Xinhao Wan; Yinlei Mao; Fengjiao Fan; Yuhong Fu; Li Wang; Liwei Mao; Yan Li; Zhuoli Li (Food Chemistry, 2025)

Multi-trophic communities in river ecosystems: Insights into environmental drivers and assembly mechanisms for ecological management— a case study in the Minjiang River - Yu Xiang; Liwei Fu; Ting Cai; Han Zhang; Wenliang Xiang; Ruxin Yang; Mengli Chen (Environmental Research, 2025)

Antilipotoxic framework nucleic acid-loaded injectable hydrogel microspheres for the targeted delivery of miR-34a-5p inhibitors to attenuate dietary fat-associated osteoarthritis - Zhichao Zhang; Liwei Fu; Yazhe Zheng; Jiang Wu; Zhixing Zhang; Chuanyang Long; Xun Yuan; ZhenGang Ding; Xiang Sui; Quanyi Guo; Sirong Shi; Shuyun Liu; et al. (Chemical Engineering Journal, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Effect of complex-grain-size curves on shear modulus degradation of calcareous sand - Liwei Wen; Zhanhu Huang; Qiang Fu; Wangfei Xie; Zhihong Huang; Yang Wu (Marine Georesources & Geotechnology, 2025)

The combined effects of soil moisture and salinity on the spatial differences of soil humification intensity in the Yangtze River estuarine wetlands - Haoyu Dong; Wenxuan Mei; Liwei Qian; Xiaoyu Gao; Haoting Liu; Xiaohua Fu; Lei Wang (Journal of Soils and Sediments, 2025)

Response of key nitrogen removal processes in estuarine salt marshes to different plant harvesting patterns varies significantly across different time scales - Wenxuan Mei; Haoyu Dong; Xiaoyu Gao; Haoting Liu; Liwei Qian; Xiaohua Fu; Lei Wang (Journal of Environmental Management, 2025)

Comammox rather than AOB dominated the efficient autotrophic nitrification-denitrification process in an extremely oxygen-limited environment - Yu Xiang; Xiaoming Song; Yilin Yang; Shuai Deng; Liwei Fu; Cheng Yang; Mengli Chen; Jia Pu; Han Zhang; Hongxiang Chai (Water Research, 2025)

Exploring the interdependencies of ecosystem services and social-ecological factors on the Loess Plateau through network analysis - Zhuangzhuang Wang; Bojie Fu; Xutong Wu; Shuai Wang; Yingjie Li; Liwei Zhang; Ni Chen; Xilin Wu (Science of The Total Environment, 2025)

Response of Water Quality to Land Use and Landscape Pattern in the Ganjiang River Watershed - Jiangang Lu; Yanmei Fu; Yuan Zhou; Liwei Zhang; Xianluo Shi (Environmental Management, 2025)

Unraveling methanogenesis processes and pathways for Quaternary shallow biogenic gas in aquifer systems through geochemical, genomic and transcriptomic analyses - Wanle Liang; Detian Yan; Mingxuan Zhang; Jikang Wang; Dong Ni; Suhe Yun; Xiaosong Wei; Liwei Zhang; Haijiao Fu (Science of The Total Environment, 2024)

Estuarine wetland tidal organic carbon activates microbial carbon pump and increases long-term soil carbon stability - Mengdi Xie; Haoyu Dong; Xiaolu Tang; Liwei Qian; Wenxuan Mei; Jianfang Yan; Xiaohua Fu; Yu Hu; Lei Wang (CATENA, 2024)

A tetrahedral framework nucleic acids-based gene therapeutic nanococktail alleviates cartilage damage and protects against osteoarthritis progression - Liwei Fu; Jiang Wu; Sirong Shi; Zhichao Zhang; Yazhe Zheng; Pinxue Li; Xun Yuan; Zhengang Ding; Chao Ning; Xiang Sui; Shuyun Liu; Quanyi Guo; et al. (Chemical Engineering Journal, 2024)

PKC-θ is an important driver of fluoride-induced immune imbalance of regulatory T cells/effector T cells - Siqi Zhu; Bingshu Liu; Guiyu Fu; Liu Yang; Dan Wei; Liwei Zhang; Qiong Zhang; Yanhui Gao; Dianjun Sun; Wei Wei (Science of The Total Environment, 2024)

Drought reduces peanut yield indirectly through regulating soil nematode community in a manipulative field experiment in central China - Cancan Zhao; Rong Fan; Xiaolin Li; Like Fan; Liwei Zhang; Xinyu Yan; Xiang Zhao; Yuan Miao; Yanfeng Sun; Yuanhu Shao; Guoyong Li; Shenglei Fu (Applied Soil Ecology, 2024)

Quantifying vegetation species functional traits along hydrologic gradients in karst wetland based on 3D mapping with UAV hyperspectral point cloud - Bolin Fu; Liwei Deng; Weiwei Sun; Hongchang He; Huajian Li; Yong Wang; Yeqiao Wang (Remote Sensing of Environment, 2024)

Soluble and insoluble fractions of soy protein isolate affect the properties of its high-moisture extrudates - Liwei Fu; Zhaojun Wang; Benu Adhikari; Zhiyong He; Maomao Zeng; Fang Qin; Jie Chen (Food Bioscience, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

Experimental Research on the Preparation of Composite Adsorbent Based on Iron Manganese Mud to Remove Sb(III) from Water - Yashu Yuan; Pengyu Cao; Liwei Zhang; Li Zhang; Di Luo; Xing Jin; Jinxiang Fu (Water, Air, & Soil Pollution, 2023)

Potential use of gluten hydrolysate as a plasticizer in high-moisture soy protein–gluten extrudates - Zhaojun Wang; Yan Ji; Liwei Fu; Hongyang Pan; Zhiyong He; Maomao Zeng; Fang Qin; Jie Chen (Journal of Food Engineering, 2023)

High-moisture extrusion of soy protein: Effects of insoluble dietary fiber on anisotropic extrudates - Qian Deng; Zhaojun Wang; Liwei Fu; Zhiyong He; Maomao Zeng; Fang Qin; Jie Chen (Food Hydrocolloids, 2023)

Tidal organic input restricts CO2 sequestration capacity of estuarine wetlands - Jianfang Yan; Xin Hu; Liwei Qian; Xiaohua Fu; Lei Wang (Environmental Science and Pollution Research, 2023)

Evolution of the Middle Jurassic paleoclimate: Sedimentary evidence from coal-bearing strata in the Santanghu Basin, NW China - Liwei Zhang; Detian Yan; Shuguang Yang; Baoqing Li; Haijiao Fu; Gang Wang; Xiangrong Yang; Bao Zhang; Wanle Liang; Junfeng Zhang (Journal of Asian Earth Sciences, 2023)

Sucrose Induced HMGR to Promote Ginsenoside Biosynthesis in the Growth of Wild Cultivated Ginseng (Panax ginseng) - Rui Ma; Baoyu Fu; Pengdi Yang; Xiaoyu Teng; Daqing Zhao; Rui Jiang; Liwei Sun (Journal of Soil Science and Plant Nutrition, 2022)

Ginsenoside Biosynthesis in Panax Ginseng with Red-Skin Disease Is Inhibited by Soil Characteristics - Rui Ma; Baoyu Fu; Shikuan Song; Chunyang Zhang; Xiajun Yuan; Tingshi Zhang; Daqing Zhao; Liwei Sun (Journal of Soil Science and Plant Nutrition, 2021)

Impacts of Canopy and Understory Nitrogen Additions on Stomatal Conductance and Carbon Assimilation of Dominant Tree Species in a Temperate Broadleaved Deciduous Forest - Yanting Hu; Karina V. R. Schäfer; Liwei Zhu; Ping Zhao; Xiuhua Zhao; Guangyan Ni; Yaxing Zhang; Huiying Ye; Wanli Zhao; Weijun Shen; Shenglei Fu (Ecosystems, 2021)

Optimization of particle swarm algorithm and its usage in calculation of hydrogeological parameter - Weiwei Fu; Liwei Zhang; Jone Bruce (Arabian Journal of Geosciences, 2021)

Magnesium Acts as a Second Messenger in the Regulation of NMDA Receptor-Mediated CREB Signaling in Neurons - Hailong Hou; Liwei Wang; Tianyue Fu; Makaia Papasergi; David I. Yule; Houhui Xia (Molecular Neurobiology, 2020)

Conversion of organic carbon from decayed native and invasive plant litter in Jiuduansha wetland and its implications for SOC formation and sequestration - Jianfang Yan; Lei Wang; Yiu Fai Tsang; Liwei Qian; Xiaohua Fu; Ying Sun; Pengfei Wu (Journal of Soils and Sediments, 2020)

The Inhibitory Effects of Nitrogen Deposition on Asymbiotic Nitrogen Fixation are Divergent Between a Tropical and a Temperate Forest - Mianhai Zheng; Wei Zhang; Yiqi Luo; Shiqiang Wan; Shenglei Fu; Senhao Wang; Nan Liu; Qing Ye; Junhua Yan; Bi Zou; Chengliang Fang; Yuxi Ju; et al. (Ecosystems, 2019)

Spatio-temporal variations of the flood mitigation service of ecosystem under different climate scenarios in the Upper Reaches of Hanjiang River Basin, China - Pengtao Wang; Liwei Zhang; Yingjie Li; Lei Jiao; Hao Wang; Junping Yan; Yihe Lü; Bojie Fu (Journal of Geographical Sciences, 2018)

Representation of critical natural capital in China - Yihe Lü; Liwei Zhang; Yuan Zeng; Bojie Fu; Charlotte Whitham; Shuguang Liu; Bingfang Wu (Conservation Biology, 2017)
Traditional means of assessing representativeness of conservation value in protected areas depend on measures of structural biodiversity. The effectiveness of priority conservation areas at representing critical natural capital (CNC) (i.e., an essential and renewable subset of natural capital) remains largely unknown. We analyzed the representativeness of CNC‐conservation priority areas in national nature reserves (i.e., nature reserves under jurisdiction of the central government with large spatial distribution across the provinces) in China with a new biophysical‐based composite indicator approach. With this approach, we integrated the net primary production of vegetation, topography, soil, and climate variables to map and rank terrestrial ecosystems capacities to generate CNC. National nature reserves accounted for 6.7% of CNC‐conservation priority areas across China. Considerable gaps (35.2%) existed between overall (or potential) CNC representativeness nationally and CNC representation in national reserves, and there was significant spatial heterogeneity of representativeness in CNC‐conservation priority areas at the regional and provincial levels. For example, the best and worst representations were, respectively, 13.0% and 1.6% regionally and 28.9% and 0.0% provincially. Policy in China is transitioning toward the goal of an ecologically sustainable civilization. We identified CNC‐conservation priority areas and conservation gaps and thus contribute to the policy goals of optimization of the national nature reserve network and the demarcation of areas critical to improving the representativeness and conservation of highly functioning areas of natural capital. Moreover, our method for assessing representation of CNC can be easily adapted to other large‐scale networks of conservation areas because few data are needed, and our model is relatively simple.

Mapping the hotspots and coldspots of ecosystem services in conservation priority setting - Yingjie Li; Liwei Zhang; Junping Yan; Pengtao Wang; Ningke Hu; Wei Cheng; Bojie Fu (Journal of Geographical Sciences, 2017)

Early Life Exposure to Ractopamine Causes Endocrine-Disrupting Effects in Japanese Medaka (Oryzias latipes) - Liwei Sun; Sisi Wang; Xia Lin; Hana Tan; Zhengwei Fu (Bulletin of Environmental Contamination and Toxicology, 2016)

Rapid extraction and purification of lumbrokinase from Lumbricus rubellus using a hollow fiber membrane and size exclusion chromatography - Tingming Fu; Fengyun Yang; Huaming Zhu; Huaxu Zhu; Liwei Guo (Biotechnology Letters, 2016)

Transcriptional Responses in Adult Zebrafish (Danio rerio) Exposed to Propranolol and Metoprolol - Liwei Sun; Fang Liu; Haigang Chen; Sisi Wang; Xia Lin; Jian Chi; Qing Zhu; Zhengwei Fu (Ecotoxicology, 2015)

Ecosystem services in changing land use - Bojie Fu; Liwei Zhang; Zhihong Xu; Yan Zhao; Yongping Wei; Dominic Skinner (Journal of Soils and Sediments, 2015)

Effects of trilostane and fipronil on the reproductive axis in an early life stage of the Japanese medaka (Oryzias latipes) - Liwei Sun; Rong Jin; Zuhua Peng; Qiwei Zhou; Haifeng Qian; Zhengwei Fu (Ecotoxicology, 2014)

Toxic Effects of Bisphenol A on Early Life Stages of Japanese Medaka (Oryzias latipes) - Liwei Sun; Xia Lin; Rong Jin; Tao Peng; Zuhua Peng; Zhengwei Fu (Bulletin of Environmental Contamination and Toxicology, 2014)

Combined Effect of Copper and Cadmium on Heavy Metal Ion Bioaccumulation and Antioxidant Enzymes Induction in Chlorella vulgaris - Haifeng Qian; Jingjing Li; Xiangjie Pan; Liwei Sun; Tao Lu; Hongyu Ran; Zhengwei Fu (Bulletin of Environmental Contamination and Toxicology, 2011)

Inhibitory effects of paraquat on photosynthesis and the response to oxidative stress in Chlorella vulgaris - Haifeng Qian; Wei Chen; Liwei Sun; Yuanxiang Jin; Weiping Liu; Zhengwei Fu (Ecotoxicology, 2009)